The Severity of COVID-19 and its Correlation with Inflammation Biomarkers - Indra, Beni; Lipoeto, Nur Indrawaty; Hardisman, Hardisman; Putra, Andani Eka; Tjong, Djong Hon; Rahman, Sukri; Yusri, Elfira; Bilhaq, Muhammad Ridho; Pratama, Yusan; Risman, Yudha (Open Access Macedonian Journal of Medical Sciences, 2022)
Introduction: Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-Cov2) or Covid-19 has been spread quickly and caused 5 million deaths until February 2022. Severe symptoms of the infection may lead to death that prompt appropriate clinical diagnosis and adequate treatment going to be necessary. Covid-19 shows a severe inflammatory response which causes an imbalance in the immune response. Therefore, circulating biomarkers that can represent inflammation and immune status are potential predictors for the prognosis of COVID-19 patients. This study aims to know the role of Neutrophil-Lymphocyte Ratio (NLR), Neutrophil Monocyte Ratio (NMR), and Lymphocyte-monocyte Ratio (LMR) as inflammatory biomarkers for the severity of Covid-19. Methodology: This study is a single-center retrospective cohort study. The sample of this study was taken by consecutive sampling with complete clinical data from 893 Covid-19 patients from Andalas University Teaching Hospital from April 2020 to September 2021. This study uses SPSS Version 25.0 for data management and analysis. Result: Most of the degrees of Covid-19 infection were mild degrees as many as 597 people with an NLR average value of 2.07 (0.27-34.50), and NMR average value of 7.86 (3-46), an LMR average value of 3.67 (0.25-25), an ANC value of 3.990 (945-45). 14,608). Most of the degrees of infection in patients with negative PCR results were moderate degrees as many as 70 people with a mean NLR value of 9.0694 (0.51-47.50), a mean NMR value of 18.6199 (1.15-47.50), and a mean LMR was 3.0324 (0.29-19.50), the ANC value was 9769.73 (1.088-37,219). There was a relationship between the degree of Covid-19 infection and the NLR value (p=0.144), as well as the LMR (p=0.000), NMR(p=0.000), and ANC (p=0.000). There was no relationship between the degree of infection in the negative PCR patient group and the NLR value (p=0.000), as well as the LMR (p=0.700), NMR(p=0.120), and ANC (p=0.90). Conclusion: The severity of Covid-19 symptoms could be predicted through inflammatory biomarkers such as NLR, LMR, and NMR.